Estudo de roteirização de veículos empregando o TransCAD: contribuição para a distribuição urbana de cargas - Paula, Miguel Ângelo Almeida Faria de (2009)
This study analyzes urban freight distribution from the wholesale distribution sector to supermarkets retail sector via TransCAD software, and the vehicle routing problem with time windows has been applied for possible delivery route optimization. TransCAD focuses on a transport system based on graph theory concepts which have been employed in this study, together with some basic concepts of distribution chain and its elements. Some parameters for the application of TransCAD have been based on information provided by a wholesale distribution company located in Uberlândia, Brazil. Such information includes vehicle type, fleet size, and average client demand. The features of the vehicle type underwent changes in four different scenarios; outputs were generated for each of these scenarios, which revealed the most effective itinerary and route settings for urban freight distribution. Even though TransCAD fails to analyze factors such as traffic conditions, vehicle freight arrangement, and average vehicle speed along a given route, the results of this study may contribute to the operation of product distribution.